Review Of Desiccant In The Drying And Air-Conditioning Application - Misha, Suhaimi; Mohd Rosli, Mohd Afzanizam; Yusof, Ahmad Anas; Ramli, Muhammad Safwan Asyraf; Haminudin, Nor Faizah; Md Basar, Mohd Farriz; Sopian, Kamaruzzaman; Ibrahim, Adnan; Abdullah, Ahmad Fazlizan (International Information and Engineering Technology Association, 2021)
Desiccant is a hygroscopic substance generally used in the dryer and air-conditioning system as a drying agent. The function of desiccant is to remove moisture from the air to reduce the humidity of the surrounding air been conditioned. This paper presents several works on the performance of desiccant material in the drying and air-conditioning application. It puts focus on the various advantages and disadvantages of the use of desiccant as a drying agent. There are some advantages of using desiccant include consistent drying and low energy usage. However, there are several disadvantages of using desiccants which are low capacity for moisture absorption and pressure drop in solid desiccant. Solar drying applications have some advantages such as being comparatively cheaper than other methods and less risk of spoiling the product. On the contrary, drying applications have disadvantages include being lower in comparison to the original foodstuff and drying foods eventually leads to shrinkage. The advantages of using desiccant in air-conditioning applications offer dehumidified fresh air to keep the building's temperature in a comfortable range and enhances water recovery efficiency. There are disadvantages such as desiccant will substantially impact the system's performance and desiccant should be cooled after completely dried.